2008
DOI: 10.1038/bjp.2008.224
|View full text |Cite
|
Sign up to set email alerts
|

The PKs PKA and ERK 1/2 are involved in phosphorylation of TH at Serine 40 and 31 during morphine withdrawal in rat hearts

Abstract: Background and purpose: Our previous studies have shown that morphine withdrawal induced hyperactivity of cardiac noradrenergic pathways. The purpose of the present study was to evaluate the effects of morphine withdrawal on site-specific phosphorylation of TH in the heart. Experimental approach: Dependence on morphine was induced by a 7-day s.c. implantation of morphine pellets in rats. Morphine withdrawal was precipitated on day 8 by an injection of naloxone (2 mg kg À1 ). TH phosphorylation was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 50 publications
5
19
1
Order By: Relevance
“…2 and 3). In agreement with these data, naloxone administration to patients with chronic opioid abuse or to morphine dependent rats results in markedly increased muscle sympathetic nerve activity, NA plasma concentrations (Peart and Gross, 2006), NA and dopamine turnover (Almela et al, 2008;Milanés et al, 2000b) and total tyrosine hydroxylase (TH) expression (Almela et al, 2008). Altogether, these results suggest that an up-regulation of TH would be expected to increase the capacity of noradrenergic neurons to synthesize NA, which could contribute to the increase in NA turnover and in the hemodynamic changes seen in the heart during morphine withdrawal.…”
Section: Hemodynamic Variables During Chronic Morphine Treatment and supporting
confidence: 77%
See 1 more Smart Citation
“…2 and 3). In agreement with these data, naloxone administration to patients with chronic opioid abuse or to morphine dependent rats results in markedly increased muscle sympathetic nerve activity, NA plasma concentrations (Peart and Gross, 2006), NA and dopamine turnover (Almela et al, 2008;Milanés et al, 2000b) and total tyrosine hydroxylase (TH) expression (Almela et al, 2008). Altogether, these results suggest that an up-regulation of TH would be expected to increase the capacity of noradrenergic neurons to synthesize NA, which could contribute to the increase in NA turnover and in the hemodynamic changes seen in the heart during morphine withdrawal.…”
Section: Hemodynamic Variables During Chronic Morphine Treatment and supporting
confidence: 77%
“…ERK signalling pathway could be important as regulator of cardiac function ) and neuronal plasticity (Adams et al, 2002). Recently, several studies have shown that this pathway contributes to naloxone-precipitated withdrawal in morphine dependent rats (Ren et al, 2004;Almela et al, 2007Almela et al, , 2008Almela et al, , 2011.…”
Section: Evaluation Of Changes In Perk1/2 During Morphine Withdrawalmentioning
confidence: 99%
“…7, A and B, phospho-Ser31 TH levels decreased in the right and left ventricle of morphine-dependent rats injected with SL327 before naloxone, compared with morphine-dependent rats treated with vehicle instead of SL327. As mentioned above, SL327 effectively reduces basal levels of phospho-ERK1/2 immunoreactivity, thereby suggesting that the decrease in phospho-Ser31 TH levels after treatment with SL327 is not caused by a nonspecific action of According to a previous study (Almela et al, 2008), 60 min after naloxone-precipitated morphine withdrawal, there were no changes in the levels of phospho-Ser31 TH (data not shown). However, rats chronically treated with morphine and given naloxone showed significant increases in phosphoSer31 TH in the right and left ventricle 90 min after the opioid antagonist injection compared with the corresponding control group receiving naloxone and with the morphinedependent animals receiving saline (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…According with these data, present results demonstrated that chronic morphine treatment decreases baseline cardiovascular parameters (MAP and HR) compared with placebo-treated rats. However, -opioid receptor blockade by naloxone in patients with chronic opioid abuse or in morphine-dependent rats unmasks these effects, resulting in markedly increased muscle sympathetic nerve activity, NA plasma concentrations (Kienbaum et al, 2001), NA and dopamine turnover (Pugsley, 2002;Almela et al, 2008), and total TH expression (Almela et al, 2008). In addition, when naloxone was injected in morphine-treated rats, there was an increase in MAP and HR, two objective and accurate measurable signs of opioid withdrawal in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation